The role of biomarkers in the diagnosis and treatment follow-up of idiopathic pulmonary fibrosis - kayıkçı, Abdullah; Alatas, Fusun; Alatas, I.Ozkan; Yıldırım, Huseyın; Ozen, Hulya (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease of unknown cause with a poor prognosis. The aim of our study is to determine the role of Krebs von den Lungen-6(KL-6),Matrix metalloproteinase (MMP)-7, Surfactant protein A (SP-A), Surfactant protein D(SP-D), vascular endothelial growth factor (VEGF) and periostin in the diagnosis of IPF and in the response monitoring of patients treated. Method: 47 IPF patients, 27 non-IPF interstitial lung disease (ILD) patients and 21 healthy individuals were included in the study. Demographic data, pulmonary function test- Diffusing capacity of the lung for carbon monoxide (PFT-DLCO) measurements, High-resolution computed tomography (HRCT) findings of the patients were recorded, and serum samples were taken. Results:While periostin and SP-A levels were not significantly different between IPF and non-IPF ILD, they were significantly higher in both IPF and non-IPF ILD compared to healthy control group (p=0.002,p=0.006 for periostin and p=0.002,p594.5 pg/ml (sensitivity 72%, specificity 76%), while the cut-off point for SP-A is found >6.62 ng/ml (sensitivity 87.2%,specificity 57.1%). In the combined ROC analysis based on SP-A=6.62 ng/ml and periostin >634.6 pg/ml values, sensitivity was found to be 85% and specificity was 57%.Considering the correlation of forced expiratory volume in the first second  (FEV1)(%), forced vital capacity (FVC)(%), restriction and diffusion severities with biomarker levels in the 6th month of IPF patients treated, a correlation was detected between MMP-7 levels and restriction severities (p=0.020), between KL-6 levels and restriction and diffusion severities (p=0.002), and between SP-A levels and FVC(%)(p=0.006).Conclusion:It is thought that biomarkers SP-A and periostin may contribute significantly to the diagnosis of patients with IPF, and SP-A, MMP-7 and KL-6 levels may contribute significantly to treatment follow-up.